Vibration Analysis of Cantilever Beam - MOHAMED ZAKKARIA, MOHAMED SALMAN BIN; Nurhafizzah Hassan (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Vibration analysis is an integral aspect of engineering, especially for structures like the cantilever beam, which have applications in mechanical, civil and aerospace engineering. Knowledge of their characteristics, like natural frequencies and mode shapes is quite important in ensuring the integrity of a structure and preventing failure by resonance. This project carries out a theoretical study on the vibration analysis of a cantilever beam with the help of LISA software-based finite element analysis. The objective is to determine the vibration frequencies and modes of the cantilever beam and evaluate the capability of FEA to provide proper and accurate results. This project starts off with an overview of the basic concepts involving mechanical vibration, assigning special emphasis on cantilever beams. Experiments are conducted to get the natural frequencies and mode shapes of the beam. The cantilever beam is then modelled in LISA software with the boundary conditions and material properties to simulate a real-life condition. Modal analysis is performed with the software to reproduce the vibration characteristics, including the first few natural frequencies and their respective mode shapes. The results of the experimental and FEA analysis are compared to validate the accuracy of the LISA software. The study shows that LISA predicts natural frequencies and mode shapes accurately, which match very well with the theoretical predictions. Besides, FEA visualization of mode shapes gives a much better insight into how the beam deforms when vibrating, something that is difficult to achieve with experimental methods alone. This study is important because it highlights the importance of vibration analysis in engineering and how a tool like LISA now can help to automate complex calculations while improving accuracy of the output.